An investigation of individual functionality football referees of high qualification - T.G. Chopilko (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose: to determine the level of individual functionality arbitrators of high qualification. Material : in the experiment participated 29 high qualification arbitrators aged 21-45 years. Results : it was found that the means and methods of special physical preparation for a competition to be insufficiently effective. Functionality of arbitrators is different. Only 8 arbitrators have a high level of functionality. Conclusions : the study of the functional state of the arbitrators is an important factor in planning their training process. Hard volume and intensity exercise at the wrong planning of the training process can lead to overtraining, reduce special physical readiness, contribute to pathological changes in the body.